Endophytic Fungi-Mediated Biocatalysis and Biotransformations Paving the Way Toward Green Chemistry - Choudhary, Malvi; Gupta, Suruchi; Dhar, Manoj K.; Kaul, Sanjana (Frontiers in Bioengineering and Biotechnology, 2021)
Nature has always been a driving force in fuelling the host-microbe coevolution that offers enormous biodiversity in areas of natural products discovery and related applications. The endophytic community, in particular, has undergone evolutionary mechanism with their host plant and has emerged as a powerful tool of genetic diversity. Endophytes are defined as omnipresent diverse group of microbes colonising the inner parts of the plants asymptomatically. In addition to being acknowledged as novel bioactive metabolite producers endophytic fungi novel have also pushed forward the frontiers of biotechnological applications. The unique repertoire of metabolites can serve as a treasure trove of biocatalysts. They are capable of catalysing organic transformations of wide range of substances generating pure compounds with biotechnological relevance. Also, they have been overlooked as promising technology in terms of reusability, stability, broad substrate specificity, recovery, recyclability and better product quality. Such an environmental and economical sustainable approach has drawn considerable attention from synthetic chemists, natural products researchers, and synthetic biologists. Additionally, the potential of endophytic fungi as biocatalyst has greatly expanded beyond the existing boundaries with the advancement in high-thoroughput screening, molecular biology techniques, metabolic engineering and protein engineering. The attractive advantages offered by fungal endophytic enzymes as biocatalyst and their significant applications has prompted a revolutionary notion in sustainable biotechnological processes. Therefore, the present review illustrates the feasible use of endophytic fungi in the area of biotransformation and biocatalysis for the synthesis of novel metabolites and pharmaceutical intermediates.